PREDICTING CHANGE IN PERCEIVED SOCIAL SUPPORT IN LATE LIFE: THE ROLE OF PERSONALITY AND GENDER. (11th November 2018) - Jacobs, C; Holtzer, R
Abstract: Perceived social support (PSS) has a uniquely beneficial effect on physical and mental health in older adults, yet relatively little is known about patterns of change in PSS during late life. While some individuals report rather stable PSS, others exhibit either increasing or decreasing levels. However, few studies have examined risk factors related to this individual-level change. Based on previous literature, we identified gender and personality (specifically neuroticism and extraversion) as primary variables of interest. Personality traits were analyzed independently and as combined Neuroticism-Extraversion quadrants for the entire sample and in stratified models in order to explore the potential moderating effect of gender. The study sample consisted of 411 community-dwelling, healthy older adults (56.2% female) who were followed for up to five years. Linear mixed effect models (LMEM) and Cox proportional hazards regression were used to examine continuous change and incidence of decline in PSS, respectively. LMEM results found that personality quadrants provided incremental information over single traits, with High Neuroticism-Low Extraversion and Low Neuroticism-Low Extraversion significantly moderating PSS decline. Additionally, stratified models found High Neuroticism-Low Extraversion and High Neuroticism alone were linked with PSS decline in males, while Low Neuroticism-Low Extraversion was linked with PSS decline in females. LMEM and Cox models suggest that while PSS decline in males is likely associated with High Neuroticism, PSS decline in females may be associated instead with Low Extraversion. Future clinical implications include earlier identification of individuals who are at risk for decreased social support, and its related impact on health.